Momentum for building a Northeast Asian economic community: emerging challenges and opportunities - Korea Institute for International Economic Policy; Cho, Lee-Jay; Jeong, Hyung-Gon (Korea: Korea Institute for International Economic Policy, 2018)
This volume in the series of proceedings volumes is titled (3z(BMomentum for Building a Northeast Asian Economic Community: Emerging Challenges and Opportunities? and comprises summaries of research presentations and discussions at the planning meeting in Honolulu, at the 27th Annual Conference of the Northeast Asia Economic Forum in Sendai, Japan, and at the Honolulu Ad Hoc Group Meeting on Financial Cooperation in Northeast Asia in 2018. s
Preface -- Contributors -- Introduction and Overview -- Statements by Country Representatives and Keynote Address -- Part 1. Building a Northeast Asia Economic Community and its Extended Regions -- Part II. Cross-boarder Infrastructure and Special Economic Zones in Northeast Asia -- Part III. Financial Cooperation in Northeast Asia -- Part IV. Energy and Environment in Northeast Asia -- Part V. Tourism Cooperation in Northeast Asia -- Part VI. Panel Discussion on Natural Disaster and Regional Cooperation -- Part VII. The Honolulu Ad Hoc Group Meeting on Financial Cooperation in Northeast Asia: Proposal for the Northeast Asia Bank for Cooperation and Development (NEABCD) Revisited -- Appendices
Includes Appendix
Keywords: Economic Community -- Northeast Asia; Economic Cooperation -- Northeast Asia